Transcriptional profiles of vaccine-induced protection in bovine herpesvirus-1 and Mycoplasma bovis-challenged bison - Goldkamp, Anna K.; Kaplan, Bryan S.; Menghwar, Harish; Kanipe, Carly R.; Boggiatto, Paola M.; Crawford, Lauren S.; Olsen, Steven C.; Briggs, Robert E.; Tatum, Fred M.; Dassanayake, Rohana P.; Casas, Eduardo (Frontiers in Veterinary Science, 2025)
IntroductionMycoplasma bovis causes chronic respiratory disease with high mortality rates in American bison (Bison bison). A recent study showed that a subunit vaccine containing M. bovis elongation factor thermal unstable (EFTu) and heat shock protein 70 (Hsp70) antigens induced immunity and enhanced protection in bison, resulting in reduced lung lesions and bacterial loads following experimental M. bovis challenge. This study aimed to characterize the transcriptional responses underlying this protection in vaccinated (n = 5) compared to unvaccinated control (n = 4) bison following M. bovis infection.MethodsTwo doses of vaccines were administered on day 0 and at 21 days post-vaccination (DPV), followed by intranasal inoculation with bovine herpesvirus-1 (BHV-1) at 36 DPV and M. bovis at 40 DPV. RNA sequencing was performed on liver, palatine tonsil (PT), retropharyngeal lymph node (RPLN), tracheobronchial lymph node (TBLN), spleen, and whole blood samples. Blood was collected at 1st vaccination (Day 0), 2nd vaccination (21 days post-vaccination), BHV-1 inoculation (36 DPV), M. bovis inoculation (40 DPV), and 1 week post M. bovis inoculation (47 DPV).Results and discussionThe greatest number of differentially expressed transcripts (DETs) (≤0.05 FDR) were found in blood at 36 DPV (123 total DETs) and in spleen (57 DETs). At 36 DPV, vaccinated animals showed upregulation of transcripts involved in in cell adhesion, T-helper cell (Th1/Th2/Th17) differentiation, and antigen processing and presentation. This signifies a robust response to the 2nd vaccine dose, which caused increased expression of CD3E, CD4, and CD8B correlating to increased T cell proliferation. Notably, transcription factors TBX21 and GATA3 were upregulated in vaccinated animals. Spleen-specific regulation included transcripts involved in innate immune response, such as LGALS3 and GBP-1. These findings highlight the robust immune response induced by the vaccine, particularly through T-cell mediated responses, demonstrating its potential to enhance protective immunity against M. bovis in bison.